Multidimensional Perspective of Poverty in Colombian Households - Medina-Hernández, Edith Johana; Sierra-Ibañez, Luis Francisco; Domínguez-Monterrosa, Andy Rafael (Sociedad y Economía, 2021)
This study analyzes the latest data of the Multidimensional Poverty Index (IPM) in Colombia, published by the National Administrative Department of Statistics (DANE); examining deprivations in the country’s households and sociodemographic variables of the people who are part of them. The aim is to characterize the conditioning factors of poverty according to regions, through a descriptive quantitative analysis and by applying the multivariate technique: Principal Component Analysis (PCA). The results obtained show that variables such as the number of household members, their educational attainment and access to formal employment determine considerable differences between households considered poor and non-poor. In addition, a preponderance of poverty circumstances is observed in the coastal regions of the country and the Amazon region.